Laparoscopic Management of Primary Ovarian Leimyoma in a Patient with Pelvic Kidney : A Case Report - Ulun Uluğ; Ali İhsan Gönenç; Özlem Dülger; Latif Küpelioğlu; Güray Kılıç (Medical Network, 2017)
Leiomyoma is one of the rarest solid tumours of the ovary. We report a case of a 35 years old woman suffering from irregular menstruel periods and solid unilateral ovarian mass managed by laparoscopic removal. Medical history of the patient is remarkable because of coexisting pelvic kidney and a history of infertility necessiating IVF treatment including gonadotropin stimulation